Austrian syndrome, ceftriaxone-induced agranulocytosis and COVID-19. Issue 1 (6th January 2021) - McCulloch, James Edward; Miller, Alexandra; Borcea, Marius; Reid, Jeremy
Abstract : We present a case of a 75-year-old woman with Austrian syndrome: pneumonia, meningitis and endocarditis all due to Streptococcus pneumoniae . Transoesophageal echocardiogram demonstrated a large mitral valve vegetation with severe mitral regurgitation. She was treated with intravenous ceftriaxone and listed for surgical repair of her mitral valve. Preoperatively, she developed an idiosyncratic drug-induced agranulocytosis secondary to ceftriaxone, which resolved on cessation of the medication. However, while awaiting neutrophil recovery, she developed an acute deterioration, becoming critically unwell. This deterioration was multifactorial, with acute decompensated heart failure alongside COVID-19. After multidisciplinary discussion, she was considered too unwell for surgery and palliated.